Kepentingan Amerika Serikat Dalam Mempertahankan proyek Naval medical Research Unit two (NAMRU 2) - Yenti Sofra Devita; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is analyzing about the presence of Naval Medical Research Unit Two (NAMRU 2) and the interests of USA government in keeping the NAMRU 2 project to be remained in Indonesia even the MoU which binds the contract between them has been expired. NAMRU 2 is a biomedical research laboratory belongs to USA Navy which examines about the infectious diseases that occurs in tropical countries, the treatment of traumatic war, and providing medical aids to disaster victims.This research applies Diplomacy theory and national interest. And this research applies qulitative methods and case study in this research. The data collected trought library research, literature studies, official docments, academic journal, mass media.According to the MoU, NAMRU 2 should finish its tenure in Indonesia in 2005, but with reasons that there still many things undone, making NAMRU 2 still want to extend the MoU with the deadline period for one year. But until 2008, NAMRU 2 is still freely conducting their activities even it should be over in 2006. Its peak, in 2008 Indonesia’s health minister at that time dr. Siti Fadilah Supari give orders to every hospital in Indonesia to not sending any virus samples to NAMRU laboratory because, according to her, NAMRU 2 has an economic motives behind the vaccines making of virus samples that delivered from every hospital in Indonesia to NAMRU 2.Keywords: NAMRU 2, virus samples, vaccine, and USA interest